Autoantigen cross-reactive environmental antigen can trigger multiple sclerosis-like disease. - Reynolds,CJ; Sim,MJ; Quigley,KJ; Altmann,DM; Boyton,RJ (Journal of Neuroinflammation, 2015)
BACKGROUND: Multiple sclerosis is generally considered an autoimmune disease resulting from interaction between predisposing genes and environmental factors, together allowing immunological self-tolerance to be compromised. The precise nature of the environmental inputs has been elusive, infectious agents having received considerable attention. A recent study generated an algorithm predicting naturally occurring T cell receptor (TCR) ligands from the proteome database. Taking the example of a multiple sclerosis patient-derived anti-myelin TCR, the study identified a number of stimulatory, cross-reactive peptide sequences from environmental and human antigens. Having previously generated a spontaneous multiple sclerosis (MS) model through expression of this TCR, we asked whether any of these could indeed function in vivo to trigger CNS disease by cross-reactive activation. FINDINGS: A number of myelin epitope cross-reactive epitopes could stimulate T cell immunity in this MS anti-myelin TCR transgenic model. Two of the most stimulatory of these 'environmental' epitopes, from Dictyostyelium slime mold and from Emiliania huxleyi, were tested for the ability to induce MS-like disease in the transgenics. We found that immunization with cross-reactive peptide from Dictyostyelium slime mold (but not from E. huxleyi) induces severe disease. CONCLUSIONS: These specific environmental epitopes are unlikely to be common triggers of MS, but this study suggests that our search for the cross-reactivity triggers of autoimmune activation leading to MS should encompass epitopes not just from the 'infectome' but also from the full environmental 'exposome.'